Найдите производные следующих функций 1. f(x) = -x^3 + 9x^2 + x - 1. Вычислите f '(-1)
2.f(x) = 1/4 * x^4 - 1/3 * x^3 + 1/2 * x^2 - 1. Вычислите f '(3)
3.f(x) = 3x-1/5x+1. Вычислите f '(1)
4.f(x) = корень из 3cosx - cos число пи/4 + 3/число пи * x^2, при x0 = число пи/3
5.Решите уравнение: f '(x) = 0 если, f(x) = x^3 - x^2 - x + 2/3
если вам не понятно могу скинуть в виде файла
Пошаговое объяснение:
1. f'(x)=-3x^2+18x+1;
f'(-1)=-3-18+1=-20
2. f'(x)=x^3-x^2+x;
f'(3)=3^3-3^2+3=21
3. 0
4.
5. 3x^2-2x-1=0
D = b2 - 4ac = (-2)2 - 4·3·(-1) = 4 + 12 = 16
x1 = (2 - √16) / 2·3 = (2 - 4)/ 6 = -2/6 = - 1/3
x2 = (2 + √16)/ 2·3 = (2 + 4)/ 6 = 6/6 = 1